PERANCANGAN PRMOSI CAFÉ DAN RESTO PONDOK RAOS MELALUI MEDIA CETAK - RERDI ARISTO, Drs. M. Nasrul Kamal, M.Sn, Dr. Yahya, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
The porposes of thi (1) to increase the quality of promotion of café and resto Pondok Raos in order to be more interesting and convenient by by designing the promotion media such a printing media. (2) to desing a booklet as the main media with the interesting and simple visual message. Determining the communicative color, typhography, and layout to the public so that Pondook Raos has its own characteristics. The sources of the data of this thesis are done by collecting data metod, such as observation, interview, and the documentary of the café and resto Pondok Raos. (3) Desingne metode use the SWOT analisis. The result of this thesis is promotion media such a simple, interesting, and communicative booklet.Key word: Pondok Raos, designe, booklet